Computer-informative software for research of the new materials of constructional applications - Kuts, Yu.; Povstyanoy, O. (Functional Materials, 2017)
This article describes the main processes of deposition of combined a protective coating on the machine parts. Characterization of the coating process, which includes electric metallization followed by synthesis, was presented. Microstructure and performance of the protective coatings for structural parts of constructional applications from powder obtained from industrial wastes were studied. The aim of this paper is to analyze the main methods to protect surfaces of constructional purposes which obtained from powder of industrial wastes and to explore the process of applying of such a coating that meets modern requirements.